2023
DOI: 10.3389/fpsyg.2023.1007970
|View full text |Cite
|
Sign up to set email alerts
|

Global education movement: English as a second language teachers’ perceptions of integrating volatility, uncertainty, complexity, and ambiguity elements in lessons

Abstract: Education evolves and progresses globally in a technology-driven world, highlighting the integration of VUCA elements of volatility, uncertainty, complexity, and ambiguity in lessons. Learners are molded to equip themselves with the world and real-life knowledge in their readiness to adapt to the VUCA world. Global education consists of preparing learners for the VUCA world. This study aimed to investigate the current English as a Second Language (ESL) teaching practices and the ESL teachers’ incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Unfortunately, she was struggling herself and failed to create a supportive and nurturing learning environment for her students to thrive. The findings are in support with (Yaccob et al, 2023) who indicated that studying in VUCA times is very overwhelming, leading to burnout and demotivation of lecturers and teachers.…”
Section: Flexible and Adapting Teaching Approachessupporting
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, she was struggling herself and failed to create a supportive and nurturing learning environment for her students to thrive. The findings are in support with (Yaccob et al, 2023) who indicated that studying in VUCA times is very overwhelming, leading to burnout and demotivation of lecturers and teachers.…”
Section: Flexible and Adapting Teaching Approachessupporting
confidence: 87%
“…Learners must also acquire competencies such as the ability to seek and synthesize information critically and take charge of their own learning. This is because the world is facing unprecedented complex challenges and problems, and learners need to be well-prepared to tackle real-life challenges (Yaccob, et al, 2023). To navigate the VUCA world, institutions that train language teachers should take a proactive approach and implement a variety of activities that focus on developing students' socio-cultural and language competencies and skills in dealing with real-life problems.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers hold a unique position in educational settings, and their perceptions or beliefs can either make or break their classroom practices (Shaiegy & Abdelrahman, 2021;Agbofa, Mensah, Opoku-Amankwaah, Kyeremeh, & Adu-Boahen, 2023;Yaccob, Yunus, & John, 2023). According to Bandura's (1977) social cognitive theory framework, teachers' beliefs are intertwined with self-efficacy, which is the teacher's attitude or perception of their "capabilities to organize and execute the course of action required to manage prospective situations" (Bandura, 1986, p. 3).…”
Section: Background To the Studymentioning
confidence: 99%